1990
DOI: 10.1007/bf00809072
|View full text |Cite
|
Sign up to set email alerts
|

The use of amphipathic maleimides to study membrane-associated proteins

Abstract: A series of amphiphilic polymethlyenecarboxymaleimides has been synthesized for use as sulfhydryl reagents applicable to membrane proteins. Physical properties of the compounds which are relevant to their proposed mode of action have been determined. By comparing rates of reaction in aqueous and aprotic solvents, the compounds have been shown to react exclusively with the thiolate ion. The effects of the reagents on three membrane-associated proteins are reported, and in two cases a comparative study has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The chemical and physical properties of the amphiphilic maleimide derivatives which we used to localize the cysteine residue on the receptor have been described by Griffiths et al (34,37). As indicated by their partition coefficients between octanol and phosphate buffer at pH 8, the maleimide derivatives with a polymethylene chain of up to 10 carbons are more soluble in the aqueous phase than in the lipid phase and their respective carboxyl groups are ionized and will not penetrate the membrane.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The chemical and physical properties of the amphiphilic maleimide derivatives which we used to localize the cysteine residue on the receptor have been described by Griffiths et al (34,37). As indicated by their partition coefficients between octanol and phosphate buffer at pH 8, the maleimide derivatives with a polymethylene chain of up to 10 carbons are more soluble in the aqueous phase than in the lipid phase and their respective carboxyl groups are ionized and will not penetrate the membrane.…”
Section: Discussionmentioning
confidence: 99%
“…They also share a similar reactivity toward ␤-mercaptoethanol. Furthermore, it has been demonstrated that all the maleimide derivatives have equal potency in inhibiting the enzyme, D-3-phosphoglyceraldehyde dehydrogenase in the soluble state, but varied in potency when the enzyme was embedded in the membrane (34). These amphiphilic maleimide derivatives have been used to probe the depth of the sulfhydryl groups within the plane of the membrane in several membrane-bound enzymes and transporter proteins (34,38,39).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations